2021
DOI: 10.1021/acs.jchemed.0c01139
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Anthropomorphism: Acting Out General Chemistry Concepts in Social Media Videos Facilitates Student-Centered Learning and Public Engagement

Abstract: This article describes the educational and public engagement outcomes of an activity called the “ChemClout Challenge” that was implemented in a general chemistry course at UC Riverside. Students worked in groups to make chemistry-themed videos, posted them to social media platforms, then voted on their favorite videos. The majority of students elected to make videos where they anthropomorphized general chemistry concepts, physically acting out principles such as ideal gas law relationships and electrolyte solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…Mitra et al (2010) reported that the use of videos in learning encourages active and deeper learning. Moreover, Hight et al (2021) found that using chemistry-themed videos helped students retain instructional concepts. Since TikTok is used by most older children, incorporating it into education has the potential to motivate them to learn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitra et al (2010) reported that the use of videos in learning encourages active and deeper learning. Moreover, Hight et al (2021) found that using chemistry-themed videos helped students retain instructional concepts. Since TikTok is used by most older children, incorporating it into education has the potential to motivate them to learn.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of this multimedia is 10 to 15 seconds. It has the potential to enhance teaching and learning due to its worldwide coverage (Hayes et al, 2020), easy accessibility (Hight et al, 2021), sustenance of student interests (Yang, 2020), and helps students develop IT soft skills (Baytak et al, 2011;Cintang et al, 2017). It nurtures student interest in science learning and creates an environment for spontaneous learning inside and outside the classroom (Nwanekezi & Kalu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, the importance of social media on youth has been studied for around a decade (Van Den Beemt et al , 2020 ). Some interesting findings include that, for example, acting out chemistry concepts in social media videos facilitates student learning (Hight et al , 2021 ). Another important issue from the social point of view is the need for a balance between practical work and work in computers, as the latter cannot be the only source of learning (Leung and Cheng, 2021 ).…”
Section: Social Media Videosmentioning
confidence: 99%
“…Currently, some popular science activities are promoted in the form of short courses. Because of time constraints, instructors are unable to fully impart science knowledge and guide inquiry and hands-on activities (Hight et al, 2021;Shu et al, 2021). Therefore, there is a paucity of information on whether popular science activities of short duration (a few hours) can help students achieve learning outcomes and motivate them for science studies.…”
Section: Effectiveness Of Popular Science Activities In Informal Curr...mentioning
confidence: 99%